Ground Coupled Heat Pumps in Mixed Climate Areas: Design, Characterization and Optimization - Montero, Álvaro; Bandos, Tatyana; Magraner, Teresa; Martos, Julio; Pardo, Nicolás; Urchueguía, Javier (IntechOpen, 2010)
None